Risiko Penggunaan Pil Kontrasepsi Kombinasi Terhadap Kejadian Kanker Payudara Pada Reseptor KB Di Perjan RS Dr. Cipto Mangunkusumo - Harianto, Harianto; Mutiara, Rina; Surachmat, Hery (Majalah Ilmu Kefarmasian, 2005)
World Health Organization (WHO) state that breast cancer is second cause of death among other cancer illness. Up to now, what become a major factor that caused the breast cancer has known yet, but it was believed that the relation of some factors can improve the risk of breast cancer. Breast cancer is believed happened because of a complicated interaction between many factors like genetic, environment and hormonal, which one of them is abundant estrogen hormone rate in women’s body. This research is aim to know the risk level that caused by the use of combination contraception pills, which is combination of estrogen and progesterone with the breast cancer risk. The research use case control method in hospital based with period of September-Desember 2004 at Perjan RS Dr. Cipto Mangunkusumo. The research results show that the user of combination contraception pills has the risk to have breast cancer 1,864 times bigger compare with them who doesn’t take that pills. However, the combination contraception pills is not the major risk factor but it’s only a light factor to increase the risk of breast cancer.